Cognitive Improvement After Aerobic and Resistance Exercise Is Not Associated With Peripheral Biomarkers - Ando, Soichi; Komiyama, Takaaki; Tanoue, Yukiya; Sudo, Mizuki; Costello, Joseph T.; Uehara, Yoshinari; Higaki, Yasuki (Frontiers in Behavioral Neuroscience, 2022)
The role of peripheral biomarkers following acute physical exercise on cognitive improvement has not been systematically evaluated. This study aimed to explore the role of peripheral circulating biomarkers in executive performance following acute aerobic and resistance exercise. Nineteen healthy males completed a central executive (Go/No-Go) task before and after 30-min of perceived intensity matched aerobic and resistance exercise. In the aerobic condition, the participants cycled an ergometer at 40% peak oxygen uptake. In the resistance condition, they performed resistance exercise using elastic bands. Before and after an acute bout of physical exercise, venous samples were collected for the assessment of following biomarkers: adrenaline, noradrenaline, glucose, lactate, cortisol, insulin-like growth hormone factor 1, and brain-derived neurotrophic factor. Reaction time decreased following both aerobic exercise and resistance exercise (p = 0.04). Repeated measures correlation analysis indicated that changes in reaction time were not associated with the peripheral biomarkers (all p > 0.05). Accuracy tended to decrease in the resistance exercise condition (p = 0.054). Accuracy was associated with changes in adrenaline (rrm(18) = -0.51, p = 0.023), noradrenaline (rrm(18) = -0.66, p = 0.002), lactate (rrm(18) = -0.47, p = 0.035), and brain-derived neurotrophic factor (rrm(17) = -0.47, p = 0.044) in the resistance condition. These findings suggest that these peripheral biomarkers do not directly contribute to reduction in reaction time following aerobic or resistance exercise. However, greater sympathoexciation, reflected by greater increase in noradrenaline, may be associated with a tendency for a reduction in accuracy after acute resistance exercise.